Immunocompetent rabbits infected with Cryptosporidium cuniculus as an animal model for anti-cryptosporidial drug testing. Issue 4 (March 2022) - Lu, Chunxia; Liu, Xianyong; Liu, Jie; Tang, Xinming; Zhu, Guan; Striepen, Boris; Suo, Xun
Graphical abstract: Highlights: Six isolates of Cryptosporidium cuniculus were isolated from rabbit farms, all belonging to the Ⅴb subtype. Two isolates (DF12 and CC1) were characterized for their infectivity in immunocompetent rabbits. The DF12 isolate was used to establish a rabbit infection model for successful evaluation of anti-cryptosporidial efficacy. Abstract: Cryptosporidium is one of the leading causes of diarrheal disease in humans and animals, which can be severe and deadly in neonates and immunocompromised hosts. Studies on the biology of Cryptosporidium and drug discovery efforts have been hindered by a number of factors including the limited availability of animal models. Here, we report the establishment and characterization of an immunocompetent rabbit model for infection with Cryptosporidium cuniculus . By testing four known anti-cryptosporidial compounds (nitazoxanide, baicalein, curcumin and matrine), we showed that the rabbit could be used as an alternative animal model for evaluating anti-cryptosporidial drug efficacy in vivo.